Variasi Leksikal pada Kelompok Waria dalam Seri Video Arif Muhammad - Ahmad Maulana Ghufar; Miftahula Rizqin Nikmatullah (PRASASTI: Journal of Linguistics, 2025)
This study aims to analyze the language variation of transgender groups in Arif Muhammad's video series and classify it based on word classes, language functions, and interpretations related to social issues contained in each data. The approach of this research is descriptive qualitative. The object of research is language variation in the form of lingual units of words which are then classified based on word classes. Data sources were obtained from three series of videos watched legally through Arif Muhammad's Youtube channel. The methods and techniques of data provision used are listening method and note-taking technique. Furthermore, the methods and techniques of data analysis used are the commensurate method with the basic technique of referential PUP and the advanced technique of differentiating conjunction (HBB). This research produced 37 data findings consisting of several word classes, including: (1) verbs, (2) nouns, (3) adjectives, (4) adverbs, (5) numeralia, and (6) pronomina. The words found in the dialog pieces have their own language functions that represent social issues. In addition, the patterns of word formation in waria language variations tend to be varied and unique.